Comparison of the Success of Two Techniques for the Endotracheal Intubation with C-MAC Video Laryngoscope Miller Blade in Children: A Prospective Randomized Study - Renu Sinha; Ankur Sharma; Bikash Ranjan Ray; Ravinder Kumar Pandey; Vanlalnghka Darlong; Jyotsna Punj; Chandralekha Chandralekha; Ashish Datt Upadhyay (Anesthesiology Research and Practice)
Background. Ease of endotracheal intubation with C-MAC video laryngoscope (VLS) with Miller blades 0 and 1 has not been evaluated in children. Methods. Sixty children weighing 3–15 kg with normal airway were randomly divided into two groups. Intubation was done with C-MAC VLS Miller blade using either nonstyletted endotracheal tube (ETT) (group WS) or styletted ETT (group S). The time for intubation and total procedure, intubation attempts, failed intubation, blade repositioning or external laryngeal maneuver, and complications were recorded. Results. The median (minimum/maximum) time for intubation in group WS and group S was 19.5 (9/48) seconds and 13.0 (18/55) seconds, respectively (p=0.03). The median (minimum/maximum) time for procedure in group WS was 30.5 (18/72) seconds and in group S was 24.5 (14/67) seconds, respectively (p=0.02). Intubation in first attempt was done in 28 children in group WS and in 30 children in group S. Repositioning was required in 14 children in group WS and in 7 children in group S (p=0.06). There were no failure to intubate, desaturation, and bradycardia in both groups. Conclusion. Styletted ETT significantly reduces time for intubation and time for procedure in comparison to nonstyletted ETT.